Blockchain and the Law - Szostek, Dariusz (2019)
This book analyses the new blockchain and Distributed Ledger Technology (DLT) in term of its impact on law, contracts and the digital economy. It discusses global legislation in the blockchain and its implications. The analysis of contracts includes the Bitcoin system and the Bitcoin Blockchain.